Institutional differences in Germany and France: Between spatial reform and persistence - Didier Paris; Evelyn Gustedt (Cities and metropolises in France and Germany, 2022)
Germany and France offer two different models of political and administrative organisation: a federal state on one side of the Rhine and a unitary state on the other, albeit one that has become more decentralised over the last 40 years. Thus, the French régions have reduced capacities for action compared to the Länder. At the local level, the administrative structure was strengthened in Germany by merging municipalities, whereas France chose to use intermunicipal structures. In contrast to the political and administrative stability in Germany, local and regional organisation in France is constantly evolving, faced with a succession of laws, the pace of which has accelerated over time. The same applies to spatial planning, which has been framed from the outset by the German Grundgesetz (GG - Basic Law), but which has undergone much more evolution on the French side, even if the loi d'orientation foncière (LOF - Basic Land Act) of 1967 and the loi solidarité et renouvellement urbain (SRU - Law on Urban Solidarity and Renewal) (2000) represent two fundamental stages. In both countries, the strategic dimension of planning has been strengthened, and each side has developed its own tools for the management of urban projects.
urn:nbn:de:0156-1119022; hdl:10419/266400; https://econpapers.repec.org/RePEc:zbw:arlfob:20
Keywords: 710; State; administrative organisation; local authorities; planning; drivers of change